The Prevalence of Visual Impairment in People with Dementia (the PrOVIDe study): a cross-sectional study of people aged 60-89 years with dementia and qualitative exploration of individual, carer and professional perspectives - Michael Bowen; David F Edgar; Beverley Hancock; Sayeed Haque; Rakhee Shah; Sarah Buchanan; Steve Iliffe; Susan Maskell; James Pickett; John-Paul Taylor; Neil O'Leary (National Institute for Health Research, 2016)
Background: The prevalence of visual impairment (VI) and dementia increases with age and these conditions may coexist, but few UK data exist on VI among people with dementia. Objectives: To measure the prevalence of eye conditions causing VI in people with dementia and to identify/describe reasons for underdetection or inappropriate management. Design: Stage 1 - cross-sectional prevalence study. Stage 2 - qualitative research exploring participant, carer and professional perspectives of eye care. Setting: Stage 1 - 20 NHS sites in six English regions. Stage 2 - six English regions. Participants: Stage 1 - 708 participants with dementia (aged 60-89 years): 389 lived in the community (group 1) and 319 lived in care homes (group 2). Stage 2 - 119 participants. Interventions: Stage 1 gathered eye examination data following domiciliary sight tests complying with General Ophthalmic Services requirements and professional guidelines. Cognitive impairment was assessed using the Standardised Mini-Mental State Examination (sMMSE) test, and functional ability and behaviour were assessed using the Bristol Activities of Daily Living Scale and Cambridge Behavioural Inventory - Revised. Stage 2 involved individual interviews (36 people with dementia and 11 care workers); and separate focus groups (34 optometrists; 38 family and professional carers). Main outcome measures.: VI defined by visual acuity (VA) worse than 6/12 or worse than 6/18 measured before and after refraction. Results: Stage 1 - when participants wore their current spectacles, VI prevalence was 32.5% [95% confidence interval (CI) 28.7% to 36.5%] and 16.3% (95% CI 13.5% to 19.6%) for commonly used criteria for VI of VA worse than 6/12 and 6/18, respectively. Of those with VI, 44% (VA < 6/12) and 47% (VA < 6/18) were correctable with new spectacles. Almost 50% of remaining uncorrectable VI (VA < 6/12) was associated with cataract, and was, therefore, potentially remediable, and one-third was associated with macular degeneration. Uncorrected/undercorrected VI prevalence (VA < 6/12) was significantly higher in participants in care homes (odds ratio 2.19, 95% CI 1.30 to 3.73; p < 0.01) when adjusted for age, sex and sMMSE score. VA could not be measured in 2.6% of group 1 and 34.2% of group 2 participants (p < 0.01). The main eye examination elements (excluding visual fields) could be performed in > 80% of participants. There was no evidence that the management of VI in people with dementia differed from that in older people in general. Exploratory analysis suggested significant deficits in some vision-related aspects of function and behaviour in participants with VI. Stage 2 key messages - carers and care workers underestimated how much can be achieved in an eye examination. People with dementia and carers were unaware of domiciliary sight test availability. Improved communication is needed between optometrists and carers; optometrists should be informed of the person's dementia. Tailoring eye examinations to individual needs includes allowing extra time. Optometrists wanted training and guidance about dementia. Correcting VI may improve the quality of life of people with dementia but should be weighed against the risks and burdens of undergoing examinations and cataract surgery on an individual basis. Limitations: Sampling bias is possible owing to quota-sampling and response bias. Conclusions: The prevalence of VI is disproportionately higher in people with dementia living in care homes. Almost 50% of presenting VI is correctable with spectacles, and more with cataract surgery. Areas for future research are the development of an eye-care pathway for people with dementia; assessment of the benefits of early cataract surgery; and research into the feasibility of specialist optometrists for older people. Funding: The National Institute for Health Research Health Services and Delivery Research programme.